Axle load variations and vehicle growth projection models for safety assessment of transportation structures - Sriramula, Srinivas; Menon, Devdas; Prasad, Anumolu M. (Transport, 2007)
The design formulations of pavements and bridges are significantly influenced by the uncertainties associated with the prevailing vehicle weight characteristics. Accurate modelling of load spectra and the estimation of possible vehicle growth and composition are the main components in the safety assessment of transportation structures. The vehicle weights from the existing traffic form the basis for load spectra development, and the vehicle projections are subjective to the socio‐economic conditions. In this paper, the methodologies of appropriate data consideration for such representation are discussed and demonstrated based on the data from India. The load spectra are also developed for vehicular data from Interstate 95 (I‐95) in New York State. In lieu of the current status of the design codes for pavements and bridges worldwide, most of the developing countries are in need of analogous models for the calibration of the design basis. First Published Online: 27 Oct 2010